Dual vocational education and training in the service society - Walden, Günter [Verfasser] (My University, 2009)
"The dual system of vocational education and training in Germany is frequently accused of failing to have achieved the leap into the knowledge and service society and of remaining too rigidly aligned to the production sector. The present paper uses the results of empirical analyses conducted by the Federal Institute for Vocational Education and Training (BIBB) as a basis for investigating whether the structures of the dual systems are, in fact, still operating in accordance with their historical origins. The results provide evidence that the increasing significance of the service sector initially brought about an attendant weakening of in-company training, although dual training has now made significant strides in developing in line with the service society. Work still remains to be done in respect of the more knowledge oriented service occupations. Of particular importance here is not to narrow down the debate to the competitive aspect of higher education." (Autorenreferat, BIBB-Doku)
Keywords: S 1.3.1 Ausbildung im Dualen System; G 2.3 Wandel von Arbeit & Wirtschaft; G 1.3.1.1 Ausbildungsstellenmarkt; G 1.2.1 Grund- & Strukturdaten des Arbeitsmarktes; S 3.5.2.2 Bundesinstitut für Berufsbildung (BIBB); Berufsausbildung; Duales System; Dienstleistungsgesellschaft; Wirtschaftsstrukturwandel; Dienstleistungssektor; Dienstleistungsberuf; Qualifikationsniveau; Beschäftigungsentwicklung; Ausbildungsangebot; Quantitative Angaben